2007
DOI: 10.1242/jcs.001016
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of polymerization and localization of calsequestrin inC. elegans

Abstract: Dual roles of calsequestrin (CSQ-1) being the Ca2+ donor and Ca2+ acceptor make it an excellent Ca2+-buffering protein within the sarcoplasmic reticulum (SR). We have isolated and characterized a calsequestrin (csq-1)-null mutant in Caenorhabditis elegans. To our surprise, this mutant csq-1(jh109) showed no gross defects in muscle development or function but, however, is highly sensitive to perturbation of Ca2+ homeostasis. By taking advantage of the viable null mutant, we investigated the domains of CSQ-1 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
14
1
1
Order By: Relevance
“…In close analogy with our results, the p.Arg33Gln mutation in CASQ2, identified in a patient with CPVT, appears also to affect a high‐affinity Ca 2+ ‐binding site and to interfere with the assembly of longitudinal polymers, resulting in increased aggregate formation [Kim et al., ]. Indeed, several studies have been performed on both CASQ2 carrying mutations found in patients with CPVT and on CASQ1 containing selected mutations addressing specific structural domains: these mutated forms of CASQ showed an anomalous polymerization behavior, increased propensity to form aggregates, and displayed altered subcellular localization with reduced Ca 2+ ‐binding ability [Wang et al., ; Park et al., ; Cho et al., ; Kim et al., ; Subra et al., ]. It would then appear that mutations that alter Ca 2+ ‐binding ability and/or polymerization may reduce the ability of CASQ proteins to remain in solution and to efficiently store Ca 2+ [Kim et al., ; Kumar et al., ].…”
Section: Discussionsupporting
confidence: 84%
“…In close analogy with our results, the p.Arg33Gln mutation in CASQ2, identified in a patient with CPVT, appears also to affect a high‐affinity Ca 2+ ‐binding site and to interfere with the assembly of longitudinal polymers, resulting in increased aggregate formation [Kim et al., ]. Indeed, several studies have been performed on both CASQ2 carrying mutations found in patients with CPVT and on CASQ1 containing selected mutations addressing specific structural domains: these mutated forms of CASQ showed an anomalous polymerization behavior, increased propensity to form aggregates, and displayed altered subcellular localization with reduced Ca 2+ ‐binding ability [Wang et al., ; Park et al., ; Cho et al., ; Kim et al., ; Subra et al., ]. It would then appear that mutations that alter Ca 2+ ‐binding ability and/or polymerization may reduce the ability of CASQ proteins to remain in solution and to efficiently store Ca 2+ [Kim et al., ; Kumar et al., ].…”
Section: Discussionsupporting
confidence: 84%
“…Studies with different combinations of deletion mutants have demonstrated that assembly of large 3‐D complexes formed by polymerization of calsequestrin monomers may be crucial for the correct targeting of this protein to the junctional SR (47,48). In addition, interaction between calsequestrin and RyR in Caenorhabditis elegans has been shown to be also important for the localization of this protein to the terminal cisternae (49). Comparative analysis of the ability of triadin deletion mutants generated in our laboratory to localize at the junctional SR has led to the identification of three putative regions responsible for the correct localization of this protein.…”
Section: From Er To Srmentioning
confidence: 99%
“…Although difficult to study in myocytes, studies of CSQ overexpression in nonmuscle cells have clearly shown how polymerization can also determine CSQ localization [1214]. In mammalian nonmuscle cells, each CSQ isoform (cardiac or skeletal muscle) undergoes polymerization that leads to its concentration in a specific cellular compartment.…”
Section: Introductionmentioning
confidence: 99%